2016
DOI: 10.1039/c6ra07741b
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic efficiency improvement in single-layer orange phosphorescent organic light-emitting devices with suppressed efficiency roll-off

Abstract: We have successfully demonstrated efficient single-layer organic light-emitting devices (OLEDs) with a current efficiency of 31.38 cd A À1 . The efficiencies still remain as high as 31.36 cd A À1 , 30.76 cd A À1 and 29.98 cd A À1 at the luminance of 1000 cd m À2 , 5000 cd m À2 and 10 000 cd m À2 . The key feature of the device concept is uniformly doping iridium-bis-(4,6-difluorophenyl-pyridinato-N,C2)-picolinate (FIrPic) into a single organic layer to balance the transport of charge carriers. To better unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Material designs for low efficiency roll-offs focus on developing high-performance host molecules of PhOLEDs with balanced hole and electron injection and transportation, ranging from bipolar small molecules, cohost systems, thermally activated delayed fluorescence (TADF) molecules, exciplex with TADF properties, etc. To our knowledge, the best results of EQE roll-offs for blue PhOLEDs are currently as low as 0.53% at 1000 cd m –2 and 4.3% at 10 000 cd m –2 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Material designs for low efficiency roll-offs focus on developing high-performance host molecules of PhOLEDs with balanced hole and electron injection and transportation, ranging from bipolar small molecules, cohost systems, thermally activated delayed fluorescence (TADF) molecules, exciplex with TADF properties, etc. To our knowledge, the best results of EQE roll-offs for blue PhOLEDs are currently as low as 0.53% at 1000 cd m –2 and 4.3% at 10 000 cd m –2 …”
Section: Introductionmentioning
confidence: 94%
“…To our knowledge, the best results of EQE roll-offs for blue PhOLEDs are currently as low as 0.53% at 1000 cd m −215 and 4.3% at 10 000 cd m −2 . 16 Here, we found that the hole-injection layer (HIL) also has a significant influence on the efficiency roll-off of PhOLEDs; by replacing the widely used poly (3,4- showing an EQE roll-off of 2% at 10 000 cd m −2 and 7% at 20 000 cd m −2 after a set of thermal and current annealing treatments. These results illustrate profound implications for the fabrication of stable blue PhOLEDs using inorganic HILs and proper annealing treatment to optimize the organic/inorganic interfaces.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, single-layer OLEDs have aroused extensive interests due to their simplest structures and superior performance [13,14]. A variety of methods have been suggested to simplify the device structure, among which adopting a bipolar organic material is an efficient one [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%